PERJANJIAN KERJA WAKTU TERTENTU (PKWT) PASCA BERLAKUNYA UNDANG-UNDANG CIPTA KERJA (analisis PKWT PT. Radiant Utama) - Fernanda Ryzkiansyah Herman, (2022)
Work agreement for a certain period of time (PKWT) is one of the provisions that underwent changes after the enactment of the Cipta Kerja Law where there was a provision for compensation for PKWT workers and the PKWT period was changed to a maximum of 5 years. Thus, the purpose of this study is to find out how the implementation of PKWT in Radiant Utama Company and to find out about the company's responsibility to PKWT workers related to compensation after the Cipta Kerja law.This study uses a normative juridical method with a statutory approach and a conceptual approach. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The result of this research is the implementation of PKWT at PT. Radiant Utama, after the enactment of the Cipta Kerja Law, the implementation of the PKWT is in accordance with what is stipulated in the Cipta Kerja Law and Government Regulation Number 35 of 2021 concerning Work Agreements for a Certain Time. But PKWT at PT. Radiant Utama there are several weaknesses related to not being listed in the PKWT agreement regarding dispute resolution, the party representing the company PT. Radian in the PKWT agreement was represented by the Human Resources and General Affairs Dept. Head (HR & GA Dept. Head) as the first party. However, it was not explained based on a power of attorney from the Board of Directors of PT. Radiant and Inside.While related to corporate responsibility. then PT. Radiant Utama has carried out its responsibilities as a company to provide compensation as stipulated in Article 16 paragraph 1 of Government Regulation No. 35 of 2021 regarding the amount of compensation. Other company responsibilities that have been carried out are related to providing wages and benefits as well as the company's responsibility to provide Employment Insurance and Health Insurance.